Determination of Lead Content in Gasoline Samples Using Flame Atomic Absorption Spectrometry (FAAS) (Comprehensive Journal of Science, 2026)
AbstractThe determination of lead content in gasoline remains essential for environmental monitoring and regulatory compliance, despite the global phase-out of leaded fuel. This study employed Flame Atomic Absorption Spectrometry (FAAS) to analyze lead concentrations in gasoline samples from four commercial brands: Petronas, Shell, Caltex, and Petron. Sample preparation involved chemical stabilization using iodine and Aliquat 336 in MIBK. Calibration was performed using lead standard solutions in the range of 0.528 to 2.642 ppm. Results indicated extremely low lead concentrations across all samples (0.1857 – 0.3697 ppm), aligning with Malaysian and international regulatory limits. Recovery tests using spiked samples yielded results within 99–106%, confirming methodological accuracy. This study reaffirms the effectiveness of FAAS for trace lead analysis and the continuing compliance of Malaysian fuel with environmental standards.
Keywords: FAAS, Gasoline, Lead, Analysis